Thiol redox biology of trypanosomatids and potential targets for chemotherapy - Leroux, Alejandro E.; Krauth-Siegel, Renate (Molecular and biochemical parasitology, 2016)
Trypanosomatids are the causative agents of African sleeping sickness, Chagas' disease, and the different forms of leishmaniasis. This family of protozoan parasite possesses a trypanothione-based redox metabolism that provides the reducing equivalents for various vital processes such as the biosynthesis of DNA precursors and the detoxification of hydroperoxides. Almost all enzymes of the redox pathway proved to be essential and therefore fulfil one crucial prerequisite for a putative drug target. Trypanothione synthetase and trypanothione reductase are present in all trypanosomatids but absent from the mammalian host which, in addition to the essentiality, renders them highly specific. The chemotherapy research on both enzymes is further supported by the availability of high-throughput screening techniques and crystal structures. In this review we focus on the recent advances and limitations in the development of lead compounds targeting trypanothione synthetase and trypanothione reductase. We present an overview of the available inhibitors and discuss future perspectives including other components of the parasite-specific redox pathway.